2020
DOI: 10.13189/fst.2020.080203
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic Practice of Complementary Food Preparation and Associated Factors among Mothers with Children Aged from 6 to 24 Months in Rural Kebeles of Harari Region, Ethiopia

Abstract: Introduction: Evidence shows that 10 to 20% of food-borne outbreaks perceptible in developing countries. The objective of this study was to assess the magnitude of hygienic practice of complementary food preparation and associated factors among mothers with children aged from 6 to 24 months in rural kebeles of Harari region, Ethiopia. The Method is a community based cross-sectional study design which was implemented on 422 of sampled mothers. Simple random sampling method was used to select those study partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…Our study result showed that the prevalence of poor complementary food preparation practice was (65.3%, 95% CI: (61.3%, 69.0%). The this nding is in line with the study conducted in Harari region ,Ethiopia (61%) (24), Tegedie Woreda, Northwest Ethiopia (66%)(4) and Bahir Dar Zuria Woreda, Northwest Ethiopia (61.1%) (8). The possible reason for similarity may be due to socio-economic similarity or the living standard of population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study result showed that the prevalence of poor complementary food preparation practice was (65.3%, 95% CI: (61.3%, 69.0%). The this nding is in line with the study conducted in Harari region ,Ethiopia (61%) (24), Tegedie Woreda, Northwest Ethiopia (66%)(4) and Bahir Dar Zuria Woreda, Northwest Ethiopia (61.1%) (8). The possible reason for similarity may be due to socio-economic similarity or the living standard of population.…”
Section: Discussionsupporting
confidence: 91%
“…The possible reason may be developing ignorance toward hygienic complementary preparation practice and feeding children when the age of mother is increasing. However, the nding is inconsistent with the study conducted in Harari region (24). The difference of these could be due to socioeconomic factors or due to errors on data since there is difference on sample size considered.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Male scored higher in their FSK than females, this might be related to the small number of enrolled females in this study. In one of the recent studies of mothers preparing complementary food [45], it was found that the prevalence of good hygienic practice of food preparation was low. Females household activities in Jordan relevant to food handling might be assessed to formulate an understanding about their FSK and the level of food protection at homes.…”
Section: Discussionmentioning
confidence: 99%
“…The other social groups could be created for the certain purposes. For the part of Rural Kebeles community of Harari Region, in Ethiopia, for example, social practitioner groups could be designed to develop the hygiene life such as handwashing with soap and water before food processing, before eating food, and after visiting toilet, in which this hygiene life does not become their habit yet for part of them [31].…”
Section: The Elaboration Of Model To Implementmentioning
confidence: 99%